2022
DOI: 10.1038/s41419-022-04853-2
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of ubiquitin-specific protease 20 in tumorigenesis and cancer therapeutics

Abstract: As a critical member of the ubiquitin-specific proteolytic enzyme family, ubiquitin-specific peptidase 20 (USP20) regulates the stability of proteins via multiple signaling pathways. In addition, USP20 upregulation is associated with various cellular biological processes, such as cell cycle progression, proliferation, migration, and invasion. Emerging studies have revealed the pivotal role of USP20 in the tumorigenesis of various cancer types, such as breast cancer, colon cancer, lung cancer, gastric cancer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 136 publications
1
17
0
Order By: Relevance
“…The finger sub-domain interacts with the ubiquitin substrate, and the palm, thumb, and active site resemble the catalytic triads as found there ( Hu et al., 2002 ). A catalytic domain with accessory domains is frequently seen in DUBs, some of which aid in target detection ( Kim et al., 2016 ).USPs are the largest amongst all DUBs subfamily that contributes to the development of various malignancies ( Clague et al., 2019 ; Li et al., 2022 ). Therefore, more research using these DUBs as a therapeutic target is necessary.…”
Section: Functional Role Of Important Dub Domains In Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…The finger sub-domain interacts with the ubiquitin substrate, and the palm, thumb, and active site resemble the catalytic triads as found there ( Hu et al., 2002 ). A catalytic domain with accessory domains is frequently seen in DUBs, some of which aid in target detection ( Kim et al., 2016 ).USPs are the largest amongst all DUBs subfamily that contributes to the development of various malignancies ( Clague et al., 2019 ; Li et al., 2022 ). Therefore, more research using these DUBs as a therapeutic target is necessary.…”
Section: Functional Role Of Important Dub Domains In Humanmentioning
confidence: 99%
“…Recent research has shown that the USP20 domain plays a crucial role in the carcinogenesis of several cancer types, including adult T-cell leukemia, breast cancer, colon cancer, lung cancer, and gastric cancer. Consequently, modulating USP20 activity can be of unique cancer therapy ( Li et al., 2022 ).…”
Section: Functional Role Of Important Dub Domains In Humanmentioning
confidence: 99%
“…USP20 promotes the tumorigenesis of several cancer types, such as breast and cervical cancer; however, it exhibits inhibitory effects on GC [ 16 ]. Past reports have indicated that USP20 overexpression inhibited cell proliferation and delayed the cell cycle transition from the G1 to S phase by stabilizing Claspin [ 43 , 170 ].…”
Section: Usps and Gcmentioning
confidence: 99%
“…Hence, DUBs have attracted attention as therapeutic targets, and DUB inhibitors have been developed, with some now in preclinical development or clinical trials [ 15 ]. To date, approximately 100 DUBs have been reported and are classified into seven subfamilies based on their sequence and structural similarities as follows: ubiquitin-specific proteases (USPs), ubiquitin carboxy-terminal hydrolases (UCHs), ovarian tumor proteases (OTUs), Jab1/MPN domain-associated metalloenzymes (JAMMs), Machado–Joseph disease proteases (MJDs), the monocyte chemotactic protein-induced protease family (MINDYs), and Zn-finger and UFSP domain proteins (ZUFSPs) ( Figure 1 ) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deubiquitinases (DUB) in the deubiquitination process remove ubiquitin chains to preserve the labeled substrate proteins (12). Ubiquitin-specific peptidase 20 (USP20) is a pivotal member of the DUB family and regulates the stability of multiple proteins via the ubiquitin-proteasome pathway (13,14). USP20 is also associated with multiple biological processes (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%